2022
DOI: 10.3390/life12020230
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Large Vessel Occlusion Detection in Acute Ischemic Stroke Using Machine Learning Methods

Abstract: The early detection of large-vessel occlusion (LVO) strokes is increasingly important as these patients are potential candidates for endovascular therapy, the availability of which is limited. Prehospital LVO detection scales mainly contain symptom variables only; however, recent studies revealed that other types of variables could be useful as well. Our aim was to comprehensively assess the predictive ability of several clinical variables for LVO prediction and to develop an optimal combination of them using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Eight studies met the inclusion criteria and were included (Figure 1 ). 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies met the inclusion criteria and were included (Figure 1 ). 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…These studies included a total of 32 prehospital stroke scales and 21 ML models. Among them, 9 prehospital stroke scales 15 , 16 , 18 , 19 , 20 , 21 and 9 ML models 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 were eligible for meta‐analysis. Included studies were published from 2018 14 onwards and conducted globally (United States, 16 , 19 Japan, 15 , 20 China 14 , 21 (2 studies each) and 1 each from Hungary 18 and Taiwan 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To comprehensively assess the predictive ability of several clinical variables for large-vessel occlusion (LVO) prediction, Tarkanyi et al retrospectively analyzed prospectively collected multicenter stroke registry data. After a univariate analysis, they used the LASSO method for feature selection to select an optimal combination of variables, and various machine learning methods (random forest (RF), logistic regression (LR), elastic net method (ENM), and simple neural network (SNN)) were applied to optimize the performance of the model [ 18 ]. Jafari et al used magnetic resonance imaging (MRI) and machine learning methods to diagnose the severity of brain tumors.…”
Section: Related Workmentioning
confidence: 99%
“…Extensive medical research has identified various risk factors associated with heart disease, including physical inactivity, poor lifestyle choices, obesity, and unhealthy diet. Additionally, certain conditions, such as high blood pressure, smoking, family history, hypertension, stress, diabetes, and high cholesterol, can further elevate the risk of heart disease [7][8][9][10][11][12]. Given the complexity and multifactorial nature of heart disease, effective prediction and prevention strategies are essential for mitigating its impact.…”
Section: Introductionmentioning
confidence: 99%